Dynamics of three dimensional flow in porous media - Nikola Konatar (Electronic Journal of Differential Equations, 2017)
We describe the dynamics of the interface between two immiscible fluids of different densities in three dimensional porous media. This generalizes previous results given in two dimensions in which existence of the stream function played a substantial role. The most important contribution of the paper is the introduction of a method which avoids usage of the stream function.